Long-term Mentoring Relationships and Extending the Impacts of the Youth Mentoring Experience into Young Adulthood, Missouri, 2017-2019 - Stelter, Rebecca ([Verlag nicht ermittelbar], 2021)
The focus of this study is on the relationship between participants in a mentoring program for youths at risk and program staff. A motive for this study is to determine the existence of a genuine long-term impact between these two groups. Although numerous mentoring programs argue that there are benefits to their existence, there had been previously little data to justify these claims. This study contains a mixture of statistical data and qualitative information.